Bank Sampah "Sedekah Sampah": Pemberdayaan Ekonomi Masyarakat Menuju UMKM Desa Bawak - Ainun Yudhistira; Muhammad Daffa Mubaroq Putra Syauqi; Yocha Daraayu Febriyana; Cintia Helin Maulud Tias; Amalia Afa Reza; Nor Aini Rizqiyah; Mukhammad Syalthut Miftah (Jurnal Imiah Pengabdian Pada Masyarakat (JIPM), 2026)
This community service program was implemented through Group 007’s Kuliah Kerja Nyata (KKN) at Universitas Islam Negeri Raden Mas Said Surakarta in Bawak Village, Cawas, Klaten Regency. It responded to the low economic utilization of household waste, especially plastic bottles and cardboard, and the absence of a community-based waste institution at the neighborhood (RW) level. The team established a waste bank named "Sedekah Sampah" through socialization, five RW-level collection points, and a partnership with waste collectors. Methods included literature review, field observation, interviews, group discussion, and documentation. The program successfully built five active collection points with clear management structures, generated additional income for RW treasuries, and raised community awareness of waste sorting. It is positioned as an initial step toward recycling-based UMKM development, following similar empowerment models, and is expected to continue independently after the KKN period with support from RW management and the village government.